PPARG dysregulation as a potential molecular target in adrenal Cushing's syndrome - Vetrivel, Sharmilee; Tamburello, Mariangela; Oßwald, Andrea; Zhang, Ru; Khan, Ali; Jung, Sara; Baker, Jessica E.; Rainey, William E.; Nowak, Elisabeth; Altieri, Barbara; Detomas, Mario; Watts, Deepika; et al. (Frontiers in Endocrinology, 2023)
Background: We performed a transcriptomic analysis of adrenal signaling pathways in various forms of endogenous Cushing's syndrome (CS) to define areas of dysregulated and druggable targets.Methodology: Next-generation sequencing was performed on adrenal samples of patients with primary bilateral macronodular adrenal hyperplasia (PBMAH, n=10) and control adrenal samples (n=8). The validation groups included cortisol-producing adenoma (CPA, n=9) and samples from patients undergoing bilateral adrenalectomy for Cushing's disease (BADX-CD, n=8). In vivo findings were further characterized using three adrenocortical cell-lines (NCI-H295R, CU-ACC2, MUC1).Results: Pathway mapping based on significant expression patterns identified PPARG (peroxisome proliferator-activated receptor gamma) pathway as the top hit. Quantitative rtPCR (qPCRQPCR) confirmed that PPARG (l2fc<-1.5) and related genes -FABP4 (l2fc<-5.5), PLIN1 (l2fc<-4.1) and ADIPOQ (l2fc<-3.3) -were significantly downregulated (p<0.005) in PBMAH. Significant downregulation of PPARG was also found in BADX-CD (l2fc<-1.9, p<0.0001) and CPA (l2fc<-1.4, p<0.0001). In vitro studies demonstrated that the PPARG activator rosiglitazone resulted in decreased cell viability in MUC1 and NCI-H295R (p<0.0001). There was also a significant reduction in the production of aldosterone, cortisol, and cortisone in NCI-H295R and in Dihydrotestosterone (DHT) in MUC1 (p<0.05), respectively.Outcome: This therapeutic effect was independent of the actions of ACTH, postulating a promising application of PPARG activation in endogenous hypercortisolism.